- 1. x2-8x+12=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=0 B) x=-2 C) x=2 D) x=-8 E) x=12
- 2. x2-8x+12=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=-6 B) x=6 C) x=-12 D) x=-8 E) x=0
- 3. x2+8x+15=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=0 B) x=8 C) x=3 D) x=-3 E) x=15
- 4. x2+8x+15=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=-15 B) x=0 C) x=-5 D) x=5 E) x=-8
- 5. x2+4x-12=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=0 B) x=6 C) x=-12 D) x=4 E) x=-6
- 6. x2+4x-12=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=0 B) x=-4 C) x=12 D) x=-2 E) x=2
- 7. x2-2x-15=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=-15 B) x=0 C) x=5 D) x=-2 E) x=-5
- 8. x2-2x-15=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=0 B) x=15 C) x=3 D) x=-3 E) x=2
- 9. 2x2+5x-3=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=0 B) x=3 C) x=5 D) x=1/2 E) x=-1/2
- 10. 2x2+5x-3=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=0 B) x=3 C) x=3 D) x=-3 E) x=-5
- 11. 6x2-19x+15=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=0 B) x=5/3 C) x=-19 D) x=-5/3 E) x=15
- 12. 6x2-19x+15=0 ¿Cuál es una de las soluciones a la ecuación anterior?
A) x=-15 B) x=3/2 C) x=19 D) x=-3/2 E) x=0
|